Comparative Study on Different Modified Techniques Used For DNA Isolation From Teeth Samples for Obtaining Optimized Output - Indresh Kumar Mishra1 , Amarnath Mishra2 , Amit C Kharkwal3 , Braja Kishore Mohapatra4 , Chittaranja (Indian Journal of Forensic Medicine & Toxicology, 2020)
DNA isolation is a process used for isolation of DNA from different types of samples using a combination of physical and chemical methods. A comparative study is made to isolate DNA from 30 teeth samples with some pre PCR and post PCR modifications in the organic Phenol: Chloroform: isoamyl alcohol, Automate ExpressTM prepfiler BTA kit and QIAamp® DNA Investigator Kit. Our result showed significant results which will be helpful in short listing the array of these techniques.